The Influence of Work Motivation and Religiosity on Teacher Performance through Commitment as Mediation at SMP NU Gresik District - chomarindariyana chomarindariyana; Eva Desembrianita; Suyoto suyoto (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2021)
This study aims to determine 1) the influence of work motivation on teacher performance 2) the influence of religiosity on teacher performance 3) the influence of work motivation on commitment 4) the influence of religiosity on commitment 5) the influence of commitment on teacher performance 6) the influence of work motivation on teacher performance by mediation commitment 7) the influence of religiosity on teacher performance by mediating commitment.This type of research is qualitative research using a saturated sample of 65 respondents. The analysis used is PLS 3.0, with endogenous variables of teacher performance, exogenous variables of motivation and religiosity, and variable as mediating commitment. The method used in collecting data is a questionnaire.Based on the results of this study, it proves that all hypotheses can be accepted (motivation, religiosity, commitment have direct and indirect influences on teacher performance). The results of the study showed significant results. Religiosity variables which have an important influence on commitment and performance are emphasized because high religiosity in a teacher will result in good performance and have an impact on high commitment. A teacher who has religiosity, he will work as well as possible because they have the belief that work is worship that expects Ridho from Allah, has a strong opinion that knowledge must be practiced and tries to make their students better because they feel that their students are entrusted which must be accountable to both parents and the organization, especially to the Almighty. The function of a teacher who is embedded in a teacher who has high religiosity assumes that the teacher must always preach, the center of knowledge and must always transfer his knowledge for the benefit of many people.Which in previous studies produced a positive but insignificant influence.It is hoped that the results of this study can add insight for the principal in improving teacher performance.